Wireless Electricity Transmission by Coupled Magnetic Resonances - Nassor, DaifAoulah; Daroesho, Ali; Alhashim, Abdalrahaman H. (Jordan Journal of Physics, 2025)
In this work, we have experimentally demonstrated the ability of transferring electrical power wirelessly using coupled magnetic resonance technique. This technique has been improved by using four resonators, thus maintaining the efficiency of transferring electricity wirelessly during the change of the transfer distance between the transmitter and the receiver coils. We also introduce the concepts of this technique, analyze the used circuit and extract the theoretical model which agrees with experimental results. We have experimentally measured the efficiency of transferred electricity at various transfer distances beginning from 30 cm to 130 cm. The efficiency was more than 50% at a distance of less than 70 cm and 22% at a distance of 100 cm. Keywords: Resonance, Coupled magnetic resonances, Resonant frequency, Coupling coefficient, Mutual induction